The Effect of Mindfulness Learning on the Social-Emotional Skills of Students at Al Madinah Islamic Center Elementary School KKMB BSD South Tangerang - Surasni Surasni; Achmad Sumali; Moch Bayu Ibrahim S (PT. Pusmedia Group Indonesia, 2026)
This study aimed to examine the effect of mindfulness-based learning on the social-emotional skills of elementary school students at SD Al Madinah Islamic Center KKMB BSD South Tangerang. The study employed a quantitative quasi-experimental design using a pre-test and post-test control group approach, supported by qualitative data from classroom observations and teacher interviews. The participants consisted of 64 elementary students divided into experimental and control groups. The experimental group received mindfulness-based learning interventions integrated into classroom activities for eight weeks, while the control group participated in conventional learning activities. Data were collected through social-emotional skill questionnaires, classroom observations, and teacher interviews. Quantitative data were analyzed using descriptive statistics, paired sample t-tests, independent sample t-tests, and effect size analysis using IBM SPSS Statistics version 27, while qualitative findings were used to support the interpretation of students’ behavioral changes during the intervention process. The findings revealed that mindfulness-based learning significantly improved students’ social-emotional skills. The experimental group demonstrated a substantial increase in post-test scores compared to the control group. Statistical analysis showed a significance value of 0.000 (p < 0.05) with a large effect size (Cohen’s d = 1.87), indicating a strong effect of mindfulness-based learning on students’ social-emotional development. Supporting qualitative findings further indicated improvements in students’ emotional regulation, learning focus, self-control, and positive social interactions during classroom activities. The study also demonstrated that mindfulness practices were relevant and effectively implemented within the context of Islamic elementary education through activities such as breathing awareness, emotional reflection, and gratitude practice. This study concludes that mindfulness-based learning can serve as an innovative pedagogical approach to support elementary students’ social-emotional development and create more emotionally supportive classroom environments